Education reform and elite education - Kariya, Takehiko; Burtscher, Michael (Education Reform and Social Class in Japan, 2013)
As meritocratic selection turned into a mass phenomenon, the idea that differential treatment based on ability constituted 'discrimination' produced widespread aversion to ranking based on scholastic achievement. This aversion included a distaste for 'elites' selected through formal schooling. Antipathy towards the winners of the ranking and selection process - referred to as juken erīto 受験エ リート (examination elites) or gakureki erīto 学歴エリート (school pedigree elites) - spread jointly with critiques of 'the diploma society' (gakureki shakai 学歴社会) and 'an education solely for taking exams' (juken kyōiku 受験教育). In trying to understand the momentum behind the education reforms of the 1990s, it must not be overlooked that sentiments of this kind formed their groundswell.